Design and analysis of a C4S DC-DC converter for sustainable solar energy systems - G. Jegadeeswari; M. Vaigundamoorthi; R. Sundar; J. S. S. L. Bharani; C. Rajarajachozhan; M. Batumalay; S. P. Manikandan (International Journal of Power Electronics and Drive Systems (IJPEDS), 2026)
Efficient DC-DC power conversion is essential for sustainable solar photovoltaic systems. Conventional converters often suffer from leakage currents, higher circuit complexity, and limited flexibility in interfacing with grid-connected inverters. This study introduced a novel hybrid DC-to-DC converter based on the C4S (coupled capacitor combined Cuk-SEPIC) converter, proposed precisely for sustainable solar photovoltaic systems. The designed converter offers a dual output in the form of a bipolar direct current (DC) bus, allowing flexible combination with grid-connected inverters that receive either unipolar or bipolar DC inputs. This setup not only enables effective transfer of power to the grid but also efficiently removes the leakage currents without the necessity of lossy DC-link capacitors from the load-side current loop. Moreover, the magnetic cores are integrated by employing the input and output coupled capacitors, which considerably minimize ripple current and ensure the capability of power extraction from the PV unit. A fuzzy logic controller is employed to dynamically adjust the converter’s action under varying load conditions and solar irradiance. The proposed topology minimizes driver circuits, reduces system complexity, eliminates leakage current without requiring lossy DC-link capacitors, and improves reliability. Simulation results demonstrate stable voltage regulation, reduced ripple, improved efficiency, and superior dynamic response compared to conventional control methods. The proposed converter demonstrates its potential as a high-performance, intelligent, and energy-efficient process innovation for modern sustainable solar energy systems.